2005
DOI: 10.3354/meps304235
|View full text |Cite
|
Sign up to set email alerts
|

Summer foraging areas for lactating New Zealand sea lions Phocarctos hookeri

Abstract: The overlap between marine mammal species and fisheries is a source of ongoing conflict and concern. This study used satellite telemetry to examine the foraging patterns of 26 lactating female New Zealand sea lions Phocarctos hookeri from the Sandy Bay colony, Enderby Island, Auckland Islands (50°50' S, 166°28' E), over 4 consecutive austral summers from 2001 to 2004. Animals were fitted with satellite-linked platform transmitting terminals (PTTs), which yielded 9200 filtered foraging locations at sea. Trips l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 34 publications
3
85
3
Order By: Relevance
“…Whatever the reasons for those contrasting results, the differences between the corrected isotopic signals of serum and blood cells clearly reveal a marked shift after parturition towards coastal, benthic prey to the detriment of off-shore, pelagic prey, as already reported for other pinnipeds (Chilvers et al, 2005). After parturition, lactating females need to satisfy the high energy requirements involved in pup rearing, particularly during the first weeks when they need to provide lipidrich milk to their pups, so they are expected to shift to highly nutritious prey.…”
Section: Discussionmentioning
confidence: 63%
“…Whatever the reasons for those contrasting results, the differences between the corrected isotopic signals of serum and blood cells clearly reveal a marked shift after parturition towards coastal, benthic prey to the detriment of off-shore, pelagic prey, as already reported for other pinnipeds (Chilvers et al, 2005). After parturition, lactating females need to satisfy the high energy requirements involved in pup rearing, particularly during the first weeks when they need to provide lipidrich milk to their pups, so they are expected to shift to highly nutritious prey.…”
Section: Discussionmentioning
confidence: 63%
“…We used data from Chilvers et al (2005) and Chilvers (2009) for comparison with our results. These studies reported the latest data available for the Auckland Islands at the 3 breeding colonies (Enderby, Dundas and Figure of Eight Islands).…”
Section: Fieldworkmentioning
confidence: 99%
“…Females at the Auckland Islands foraged within a wide continental shelf (narrower on the west of the group of islands, see maps in Chilvers et al [2005]), mostly at the edge of the shelf or above the continental slope.…”
Section: Comparison Between the Otago Peninsula And The Auckland Islandsmentioning
confidence: 99%
See 2 more Smart Citations